Genetic evidence further elucidates the history and extent of badger introductions from Great Britain into Ireland. Issue 4 (1st April 2020) - Allen, Adrian; Guerrero, Jimena; Byrne, Andrew; Lavery, John; Presho, Eleanor; Courcier, Emily; O'Keeffe, James; Fogarty, Ursula; Delahay, Richard; Wilson, Gavin; Newman, Chris; Buesching, Christina; et al.
Abstract : The colonization of Ireland by mammals has been the subject of extensive study using genetic methods and forms a central problem in understanding the phylogeography of European mammals after the Last Glacial Maximum. Ireland exhibits a depauperate mammal fauna relative to Great Britain and continental Europe, and a range of natural and anthropogenic processes have given rise to its modern fauna. Previous Europe-wide surveys of the European badger ( Meles meles ) have found conflicting microsatellite and mitochondrial DNA evidence in Irish populations, suggesting Irish badgers have arisen from admixture between human imported British and Scandinavian animals. The extent and history of contact between British and Irish badger populations remains unclear. We use comprehensive genetic data from Great Britain and Ireland to demonstrate that badgers in Ireland's northeastern and southeastern counties are genetically similar to contemporary British populations. Simulation analyses suggest this admixed population arose in Ireland 600–700 (CI 100–2600) years before present most likely through introduction of British badgers by people. These findings add to our knowledge of the complex colonization history of Ireland by mammals and the central role of humans in facilitating it.